PENERAPAN BIMBINGAN KONSELING DALAM KURIKULUM 2013 MELALUI OTONOMI PENDIDIKAN PADA PELAKSANAAN OTONOMI DAERAH - S. Waji D.P (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2015)
Education autonomy represent the effort of enableness of education organizer includingGuidance and Counseling. In improving quality of education face various challenge of increasedistrict autonomous. Quality of education not only measured from high and lower the result offinal exam and much graduated, but quality of education have to be measured by how thegraduated can overcome and finish their problem of its life, and give the satisfaction to stakeholder. Guidance and Counsellor as education organizer must be powered to increase the quality ofeducation especially in district autonomous. Educatin of guidance and counseling must increasethe role and optimal of potency and interest as a professional of guidance and consellingKeywords : Counseling, curriculum 2013, Educational Autonomy, The autonomy of the region, Stake holder.